Proceso de Atención de Enfermería en paciente femenino con esquizofrenia paranoide. - Romero Vasquez, Bella Gabriela (2022)
In this clinical case study based on paranoid schizophrenia, which is defined as a very serious disorder that affects the individual in the way he/she acts before society, thinks and feels, a person suffering from this disorder may present difficulties in recognizing what is true and what is fictitious, causing rejection or low acceptance in society, which alters his/her sentimental expressions, becoming more acute in complex social contexts. This type of paranoid schizophrenia is primarily related to hallucinations, the auditory type, based on perception alterations, there are no language alterations or other symptoms. In the current clinical case we analyzed the case of a 46-year-old female patient who is received in the emergency area and at the moment is conscious, awake, with incoherent speech, disoriented, drowsy, restless, and sometimes presents alterations in her emotional state and hallucinations, does not refer to family company, is found on a busy road performing violent acts, at the moment she is with means of execution. In conclusion, it was possible to apply the nursing care process in female patient with paranoid schizophrenia, in addition to making the necessary interventions based on the severity of the case and in reference to the clinical picture.